HUBUNGAN POLA ASUH ORANGTUA DENGAN KEMATANGAN EMOSI REMAJA DI SMK NEGERI 2 SEWON BANTUL YOGYAKARTA - Khoirul Azizah, Bety Agustina Rahayu (AKPER Pemkab Purworejo, 2022)
Background : Adolescence is the peak point of emotionality, where there is emotional development, physical growth, especially the sexual organs that affect the development of new emotions or feelings and impulses experienced, such as feelings of love, longing, and the desire to get acquainted more intimately with the opposite sex. During this period of development, adolescents will be exposed to mental and emotional problems. Emotional mental health problems often occur in adolescence including psychosexual changes, peer influence, moral development disorders, stress in adolescence, high-risk behavior.Purpose : This study aims to determine